دور قناة الجزيرة في تشكيل الوعي السياسي حول طوفان الاقصى لدى الطلبة الجامعيين دراسة ميدانية على عينة من طلبة الاعلام لجامعة الوادي - كور رانيا; مسعود براشد (جامعة الوادي - University of Eloued, 2025)
" تعد هذه الدراسة واحدة من البحوث الوصفية المسحية في مجال الاعلام والاتصال، حيث تهدف هذه الدراسة الى معرفة دور قناة الجزيرة في تشكيل الوعي السياسي حول الطوفان الاقصى لدى الطلبة الجامعيين، وتم اسقاط الدراسة النظرية على دراسة عينة من طلبة الاعلام بجامعة الوادي، وطرحت هذه الاشكالية التالية: ما مدى مساهمة قناة الجزيرة في تشكيل الوعي السياسي لدى الطلبة الجامعيين للاعلام بجامعة الوادي حول طوفان الاقصى؟ ولتحقيق هذا الهدف تم اعتماد على المنهج الوصفي المسحي، كونه يستهدف تسجيل وتحليل وتفسير الظواهر الاعلامية والاجتماعية، كما تم الاستبيان كأدات أولية لجمع البيانات، الى جانب الملاحظة كأداة مساعدة، وقد تم تحديد حجم العينة ب ( 66) طالبا من طلبة الاعلام بجامعة الشهيد حمه لخضر بولاية الوادي، والذين بدورهم قاموا بالاجابة على الاستبيان. وقد أصفرت الدراسة الى العديد من النتائج، من أبرزها: أن قناة الجزيرة تساهم في رفع مستوى الوعي السياسي لدى طلبة الإعلام الجامعيين، وأن اتجاهات عينة الدراسة جاءت إيجابية تجاه التغطية الإعلامية التي تقدمها قناة الجزيرة لقضية طوفان الأقصى، كما أظهرت النتائج اهتمامًا ملحوظًا من قبل طلبة الإعلام بمتابعة برامج قناة الجزيرة، وإقبالًا متزايدًا على تتبع مستجدات أحداث طوفان الأقصى، وأكدت الدراسة أن قناة الجزيرة تلعب دورًا فعّالًا في تشكيل الوعي السياسي لدى هؤلاء الطلبة من خلال تغطية مفصلة للأحداث، ما ينعكس على سلوكياتهم ويعزز من فهمهم وتحليلهم للأحداث وآرائهم السياسية. "This study is one of the analytical studies in the field of media and communication. It aims to understand the role of Al Jazeera in shaping political awareness among university students regarding the Al-Aqsa Intifada. The theoretical study was applied to a sample of media students at El Oued University, and the following question was posed: To what extent did Al Jazeera contribute to shaping political awareness among university media students at El Oued University regarding the Al-Aqsa Intifada? To achieve this goal, the descriptive analytical approach was adopted, as it aims to record, analyze, and interpret media and social phenomena. A questionnaire was used as a primary tool for data collection, along with observation as a supporting tool. The sample size was determined at (66) media students at the University of Martyr Hama Lakhdar in El Oued Province, who in turn responded to the questionnaire. The study yielded several findings, most notably: Al Jazeera contributes to raising the level of political awareness among university media students, and the study sample's attitudes toward Al Jazeera's media coverage of the Al-Aqsa Flood. The results also showed a significant interest among media students in following Al Jazeera's programs and an increasing interest in tracking developments related to the Al-Aqsa Flood. The study confirmed that Al Jazeera plays an effective role in shaping the political awareness of these students through its detailed coverage of events, which is reflected in their behavior and enhances their understanding and analysis of events and their political opinions. "
مذكرة ماستر قسم اعلام واتصال تخصص السمعي البصري
Keywords: طلبة الاعلام بجامعة; الطوفان الاقصى; الوعي السياسي; قناة الجزيرة; Keywords: Al Jazeera; political awareness; Al-Aqsa Flood; media students at Al-Oued University; Palestine.